2022
DOI: 10.18343/jipi.28.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Value and Phytochemical Screening of Gembolo (Dioscorea bulbifera L.) Bulbils and Tubers from Bogor, West Java

Abstract: Gembolo is often cultivated in tropical areas, mainly for its bulbils (edible aerial bulbs) and tubers. This study will discuss the nutritional value and phytochemical screening of gembolo bulbils and tubers from Bogor, West Java. There is still little information and publication about this gembolo bulbils and tubers. In addition, to reintroduce and preserve this rare plant. The research was done by exploration, direct observation, and interview, followed by laboratory analysis and literature. The methods used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Dioscorea bulbifera L., commonly referred to as the air potato, air yam, bitter yam, cheeky yam, potato yam, is a dioecious herbaceous climber belonging to the yam family, Dioscoreaceae ( Coursey, 1967 ; Kundu et al., 2021 ). This species is native to Africa and Asia, but has widely naturalized and is cultivated across various regions, including Central and South America, Nepal, China, the Americas, the West Indies, Pacific Islands, Southeast Asia, and even parts of Australia ( Coursey, 1967 ; Guan et al., 2017 ; Kundu et al., 2021 ; Kuncari, 2022 ). This species is characterized by a twining stem with a sleek surface and alternately arranged vibrant green leaves in a broadly cordate shape ( Burkill, 1960 ; Ding and Gilbert, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dioscorea bulbifera L., commonly referred to as the air potato, air yam, bitter yam, cheeky yam, potato yam, is a dioecious herbaceous climber belonging to the yam family, Dioscoreaceae ( Coursey, 1967 ; Kundu et al., 2021 ). This species is native to Africa and Asia, but has widely naturalized and is cultivated across various regions, including Central and South America, Nepal, China, the Americas, the West Indies, Pacific Islands, Southeast Asia, and even parts of Australia ( Coursey, 1967 ; Guan et al., 2017 ; Kundu et al., 2021 ; Kuncari, 2022 ). This species is characterized by a twining stem with a sleek surface and alternately arranged vibrant green leaves in a broadly cordate shape ( Burkill, 1960 ; Ding and Gilbert, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cui and others [23] investigated the effect of D. bulbifera bulbils on the immune system of mice and reported that high dose D. bulbifera administration could considerably suppress the phagocytosis of the mononuclear macrophages. Kuncari [24] extracted steroid diosgenin, an active component of birth control pills from Dioseorea bulbifera plant. Dioseorea bulbifera contains diosgenin used for the commercial synthesis of cortisone [25].…”
Section: Introductionmentioning
confidence: 99%